BAHASA POLA PERGERAKAN KOMODITI BERAS KABUPATEN KLATEN: POLA PERGERAKAN KOMODITI BERAS KABUPATEN KLATEN - Herna, Herna (ReTII, 2021)
In Media Indonesia Monday, June 7, 2021, it was stated that Dinas Pertanian Ketahanan Pangan dan Perikanan (DPKPP) of Klaten Regency, Central Java, continues to boost the production of agricultural food crops in order to improve regional food security. Meanwhile, Klaten as Central Java's rice barn and national food buffer is now developing the concept of technology-based integrated agriculture and the application of correct cropping patterns. In determining the policy there are some data needed, such as traffic movement data. The data is used as material for analysis to formulate transportation policies in various regions in an effort to facilitate the demand for movement of goods. These transportation policies are used to improve transportation equipment as a form of intervention from the supply side on the road network. Because there is no recapitulation of the movement of rice commodities in Kabupaten Klaten as a tool for determining policy by the local government in determining several policies, it is necessary to analyze the movement of goods transport traffic in Kabupaten Klaten.. Methods This research uses descriptive quantitative research methods with secondary data analysis (ADS) approach. ADS is a method by utilizing secondary data as the main data source. Utilizing secondary data in question, namely by using an appropriate statistical test to obtain the desired information from the material body or from mature data obtained from certain Agencies or Institutions (such as BPS, Departments or Educational Institutions) to be processed systematically and objectively. The secondary data used in this study is survey data that has been conducted by the Ministry of Transportation, the Transportation Research and Development Agency, Survey of Origin and Destination for Goods Transportation in 2018. The volume of movement of goods transporting rice commodities from Klaten Regency to regencies in Central Java Province is 93,362 tons/month and from regencies in Central Java to Klaten Regency is 94,198 tons/month. The number of movements is recapitulated according to the results of a survey conducted by ATTN, Ministry of Transportation, Research and Development Agency. Keywords: Freight Transportation, Kabupaten Klaten, Movement Pattern